An Efficient Reanalysis Method for Topological Optimization of Vibrating Continuum Structures for Simple and Multiple Eigenfrequencies. (5th November 2018) - Sun, Youhong; Zhao, Xuqi; Yu, Yongping; Zheng, Shaopeng
Abstract : This paper shows how the reanalysis method can be utilized for speeding up the optimized process in topology optimization related to vibrating structures for simple and multiple eigenfrequencies. The block combined approximation with shifting (BCAS) method is used for reducing the computational effort included in repeated solution of eigenvalue problem, which will dominate a lot of the CPU time, especially for large problems. By utilizing Level 3 Basic Linear Algebra Subprograms (BLAS), the computation efficiency of the BCAS method is improved. For achieving an accurate optimal result, two indicators are presented to control the approximate reanalysis procedure. The effectiveness of the proposed method is demonstrated by three numerical examples.